PEMBUATAN TEPUNG MILLET TERFERMENTASI DAN PEMANFAATANNYA DALAM PRODUK MIE KERING - Atmaja, Rohmat Priya; Sari, Rewanda Yunita (Jurnal Teknologi Hasil Pertanian, 2017)
Millet is one of the cereals which is not much used for food product because millet has a small seed and a thick husk so its difficult to isolation of amylum starch. Fermentation of millet with mocaf A enzyme witch produced by Lactobacillus plantarum haved cellulolytic and pectinolytic activities and produce tannase it can improve the millet flour characteristic. Fermented millet flour is used to make noodle. The research aims are to find fermented millet flour process and the usage of fermented millet flour for dry noodle and organoleptic and chemical analysis of noodle substitute fermented millet flour. The process of noodle substitute fermented millet flour started with makes fermented millet flour and mixed fermented millet flour with high protein wheat flour, an egg, salt, sodium carbonate, CMC, and water. The result of organoleptic analysis dry noodle substitute fermented millet flour are panelist gave a like respons to color (5,25), texture (5,0), taste (4,7), odor (4,7) and overall panelist gave a like respons (5,05).The water content of dry noodle substitute fermented millet flour is 2% and negative result for qualitative tannin analysis.